Variabilidade genética de Aedes aegypti (Diptera: Culicidae) no estado de Sergipe - Steffler, Lizandra Makowski (2012)
Aedes aegypti is an important vector of human arboviruses as dengue, yellow fever and chikungunya in several tropical and subtropical countries. Studies of population genetic on Ae. aegypti has been growing in recent years and several molecular markers has been used to assess genetic variability of this vector. Among the molecular markers used is the ISSR (Inter-Simple Sequence Repeat) based on the use of nonspecific primers as microsatellites, and SNP (Single Nucleotide Polymorphism) that detect single base mutations in the chain of nitrogenous bases. The aim of this study was to determine the genetic variability in Ae. aegyti populations in the State of Sergipe through the molecular markers ISSR and SNP. Mosquito samples were caught using ovitraps in seven cities of Sergipe State: Canindé de São Francisco, Carira, Pinhão, Neópolis, Maruim, Aracaju and Umbaúba. DNA from adult mosquitoes was extracted and amplified with two ISSR primers and nine SNP markers. For ISSR marker analysis AMOVA resulted in 32% of genetic variation among populations and 68% within the population. The value of phiST was equal to 0.3225 indicating high genetic structure among populations. The dendrogram generated by UPGMA grouped the populations into two clusters that showed 61% similarity. The Mantel test by means of partial correlation between genetic distances and road excluding the interference of population size of the city was significant (r = -0.5399, p = 0.0359), assuming the occurrence of gene flow between Ae. aegypti populations passively by human action. For the marker SNP AMOVA analysis revealed genetic differentiation of FST = 0.07354 (p <0.01) and genetic diversity of 7.35% among populations. The analysis, showed the existence of two clusters based on genotypic similarities. For this analysis we found genetic differentiation between populations located in the countryside and on the coast. Both markers were efficient for the genetic study of natural populations of Ae. aegypti and able to differentiate among samples on a geographic scale from 30km to 240km.